1999
DOI: 10.1177/004051759906900403
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in Hemp Fibers as a Result of Enzymatic Hydrolysis with Mixed Enzyme Systems

Abstract: Hemp fabric is hydrolyzed with cellulase, hemicellulase/cellulase, and cellulase plus additional β-glucosidase. The effect of the admixture of hemicellulase and β-glucosi dase is evaluated in terms of hydrolysis rate and product properties. The influence of mechanical action during the treatment is also taken into account. Treated samples are characterized by weight loss per incubation time, tensile strength, crystallinity, acces sibility, and pore structure. The admixture of hemicellulase and,β-glucosidase pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 6 publications
2
48
0
7
Order By: Relevance
“…Similar findings on the bioscouring of hemp have been reported 16 : pectinase smoothed the fibre surface, removed pectin, and increased the surface area as well as the pore size. However, it also appreciably decreased the tensile strength when the incubation time was more than 5 h. The cellulase-catalysed hydrolysis reaction removes readily accessible surface fibrils yielding yarns more compliant in bending 5 ; the friction between fibres is altered due to the smoother fibre surface. For short treatment times, only the early stage of hydrolysis occurs and the tensile strength remains mostly unaffected.…”
Section: Tensile Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings on the bioscouring of hemp have been reported 16 : pectinase smoothed the fibre surface, removed pectin, and increased the surface area as well as the pore size. However, it also appreciably decreased the tensile strength when the incubation time was more than 5 h. The cellulase-catalysed hydrolysis reaction removes readily accessible surface fibrils yielding yarns more compliant in bending 5 ; the friction between fibres is altered due to the smoother fibre surface. For short treatment times, only the early stage of hydrolysis occurs and the tensile strength remains mostly unaffected.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…We planned the investigation of the use of enzymes in the hope that they would offer an acceptable alternative to metal salts with the advantages of being biodegradable and effective at low temperatures and with small quantities of added chemicals. It was found that enzymatic treatments www.scienceasia.org 5 , about which further investigation may shed some light.…”
Section: Dyeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dodatnim kardiranjem postiže se smanjenje finoće vlakana za oko 63 % i dužine za 87 %. Enzimski modifikovana vlakna konoplje odlikuju se povećanim sadržajem celuloze, uz smanjenje sadržaja pratećih supstanci i to hemiceluloze za 28 %, pektina za 98 % i lignina za 23 %, čime se postiže njihova dobra ispredivost na mašinama za predenja pamuka i vune [31,38]. Ipak, treba reći da se radi o skupom i zahtevnom postupku modifikovanja vlakana.…”
Section: Dobijena Duga I Kratka Vlakna Predena Su Po Sistemu Predenjaunclassified
“…Usled sve strožijih ekoloških propisa, upotreba enzima u tekstilnoj industriji u poslednje vreme sve više dobija na značaju. Enzimi se u oblasti modifikovanja vlakana konoplje, koriste kao sredstva za bio-oplemenjivanje [185][186][187]. U okviru biohemijskih postupaka [189].…”
Section: Postupci Modifikovanja Vlakana Konopljeunclassified